A General Model for Production and Operations Systems - Reisman, Arnold; Buffa, Elwood S. (Management Science, 1964)
This paper presents a structural and a mathematical framework for the analysis and/or synthesis of a large class of production systems. Service and/or goods producing enterprises are considered to be production systems. The structural framework consists of a generalized schematic involving materials, energy, capital equipment, populations, orders, information and cash flows through transducing, policy, etc., operations. This framework recognizes feedback concepts. The mathematical framework consists of sets of k node or junction equations, m potential or branch equations, and n economic evaluation equations and a methodology for their application. These equations provide for nonlinear and transient behavior and recognize the time value of money. The applicability of this model is demonstrated by industrially validated studies in the areas of manufacturing, hydraulic, heat transfer, and electrical systems analysis. The mentioned examples, though quite complex in nature, are shown to be special cases of this model.